Atividade de inseticidas sobre a broca-do-café, Hypothenemus hampei (Coleoptera: Curculionidae, Scolytinae) - Metellus, Dieudilait (2019)
The berry borer of coffee, Hypothenemus hampei (Ferrari, 1867) (Coleoptera: Curculionidae, Scolytinae), is the key pest in the coffee growing world, accounting for significant losses. With the use ban of the insecticide endosulfan in Brazil in 2013, its management has become more difficult. Thus the objective of this work was to evaluate the topical, residual and agronomic effects of the insecticides Voliam Targo, Benevia, Lorsban 480 BR, Curbix 200 SC, Sperto, Verismo, Polytrin 400/40 CE, Curyom 550 EC, Polo 500 SC and Vertimec 18 EC in the control of the berry borer of coffee (H. hampei). The experimental design was completely randomized and four replicates were used in the trials. In the laboratory, a direct spray was sprayed on the insect (topical effect) and applied to the fruits of the coffee (residual contamination). In both experiments, each plot consisted of a Petri dish lined with filter paper, 10 fruits in the green stage and 10 adult females of the berry borer, originating from artificial breeding. Two field experiments were carried out at Campus Glória Experimental Farm. The first one was carried out with the objective of evaluating the residual effect of the insecticides on artificial infestation of the berry borer after applying the products to fruits at the beginning of maturation. The number of perforated fruits, dead females, number of eggs and larvae were evaluated in laboratory and field experiments. The second field experiment had as objective to evaluate the effectiveness in controlling the natural population of the berry borer. Two applications were performed with a 30-day interval, using a motorized turbocharger. The number of fruits bored in 50 fruits per plot and percentage of seeds bored in a sample of 250 seeds per replicate were evaluated. In the laboratory, all insecticides provided mortality higher than 80% in topical application and greater than 73% by residual contamination, except the insecticide Polo 500 SC, which provided a 55% mortality. In the field experiment with artificial infestation, all the insecticides differed from the control, maintaining residual control until 30 days after application and with mortality higher than 70%, reaching up to 100% of mortality. In the test with natural berry borer females infestation the insecticides differed from the control in all evaluated parameters, showed efficacy higher than 75% at 35 days after the second application. The insecticides Voliam Targo, Lorsban 480 BR, Curbix 200 SC, Sperto, Polytrin 400/40 CE and Verismo presented the best control results, being indicated for use in the management of the berry borer of coffee.